MoCRiL: Pacini's experiment in a modern and educational way. Issue 1 (1st February 2023) - Liguori, D.; Passarelli, D.; Schioppa, M.; ,
Abstract: The MoCRiL (Measurements of Cosmic Rays in Lake) project has re-proposed, in an educational way and using modern measuring instruments, Domenico Pacini's experiment for determining the origin of the natural ionizing radiation that surrounds us in any instant. The students of 4 different schools from Calabria Region with the collaboration of the INFN researchers (OCRA collaboration of Cosenza [1]) and of the Physics department of UNICAL, performed the measurement of the ionizing particle rate at different depths in the waters of the Arvo Lake in the Sila plateau (1300 m asl). The aim of this project is to let students know and understand the often very difficult way that leads to scientific discovery, sharing ideas and results with other students, from different years and schools, and with teachers and researchers.